Critique, Dialogue, and Action: Museum Representation in Black Panther. Issue 1 (1st July 2021) - Dine, Susan
Abstract: In recent decades, the museum world has devoted time and resources to studying the opinions and actions of their visitors; however, it is much more difficult to access perspectives of a more general public that includes non-visitors. This article situates popular visual culture as a form of engagement between museum professionals and the public. By analyzing the museum scene of the Marvel Studios movie Black Panther, as well as responses to it, and then contextualizing these within the history and current events of the museum field, I identify ways in which popularly received visual culture can spur change in other cultural industries—creating productive critiques that can evolve into impactful dialogue and action to model responsive research and more inclusive museum practices.